2018
DOI: 10.1016/j.jsha.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hyper-homocysteinemia with coronary artery disease in absence of conventional risk factors among young adults

Abstract: Hyper-homocysteinemia has positive correlation with coronary artery disease among young adults in the absence of conventional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Additionally, the results of a few available studies were conflicting. A case–control study carried out among patients aged < 40 years showed a positive correlation between HHCY and CAD occurrence [ 21 ]. In comparison, another study showed no difference of serum HCY level between healthy controls and young AMI patients aged ≤ 35 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of a few available studies were conflicting. A case–control study carried out among patients aged < 40 years showed a positive correlation between HHCY and CAD occurrence [ 21 ]. In comparison, another study showed no difference of serum HCY level between healthy controls and young AMI patients aged ≤ 35 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific targets to increase the availability of methyl donor include acceleration of the conversion from homocysteine to methionine. Abnormally high levels of homocysteine have been reported to be a significant risk factor for the development of a wide range of diseases such as in cerebrovascular diseases [ 241 , 242 , 243 , 244 ], various CVDs [ 245 , 246 , 247 , 248 , 249 ], cognitive impairment including Alzheimer’s disease [ 250 , 251 , 252 ], fractures [ 253 , 254 , 255 ], and mortality [ 256 ]. Deficiencies of vitamin B12, folate, or vitamin B6 seem to play an important role in the occurrence of hyperhomocysteinemia, because they are essential for homocysteine metabolism ( Figure 2 ), and treatment with B-vitamin supplementation (B6, B12, and folate) has been demonstrated to effectively lower homocysteine levels [ 257 , 258 , 259 , 260 , 261 ].…”
Section: Nutrients and Their Metabolites And Enzymes Related To Dnmentioning
confidence: 99%
“…Similar comparable findings were observed in Pakistani subjects where 63.2% were from rural area and 36.8% from urban. Prevalence of hyperhomocystenemia was documented as higher in northern population and male patients,15 and hyperhomocystenemia has positive correlation with coronary artery disease 16. Moreover, majority of our population lives in rural area 17.…”
Section: Discussionmentioning
confidence: 70%